EFFECT OF ART AND CRAFT ACTIVITY ON QUALITY OF LIFE ENHANCEMENT IN THE ELDERLY: The objective is to study the effect of Model Arts and crafts activity for enhance the quality of life in the elderly. - Kaewsriton, Jiraphat (Life Sciences and Environment Journal, 2019)
The experimental research aimed to create and develop a model of art and craft activity as well as study the effect of the activity for enhancing the quality of life in the elderly. It was used The One Group Pretest Posttest Design among 30 voluntarily elder persons in Phlai Chumphon elderly school. This sample group was selected by purposive sampling. Tool used for this research were a model of art and craft activity for enhance the quality of life in the elderly, quality of life scale, performance skill evaluation forms and satisfaction questionnaires. Data analysis was descriptive and inferential statistics. The experimental results showed that the quality of life of the elderly who participated in art and craft activities was at high level (= 4.09, S.D. =0.45). The elderly persons were satisfied with participation in the art and craft activities at the highest level (= 4.60, S.D. = 0.32) with the operational skills at the good level. As the result, the study showed that after participating in art and craft activities, the experimental group had higher mean scores of the quality of life than the baseline at a 0.05 statistical significance level.